Las The Influences and Traces of Chinese Culture in Cuba: 1847-1959 - Lei, Chunyi (2021)
Chinese immigration to Cuba has a history of over 150 years. Under the influence of these migrants, the Cuban community has inherited some elements of this culture to some extent. Over time, the Chinesetraditions and customs have been incorporated into the island of Cuba, forming part of its multicultural identity. In this paper, from a sociocultural perspective, we present an analysis about the Chinese community in Cuba from the 19th century to 1959, and explore some prominent traces in the following seven aspects: cuisine, medicine, religion, festivals, music, sports and games of chance, as well as their roles in the formation of the local identity in the Cuban society. In this investigation, we observe this Chinese community fromthe standpoint of immigrants, taking into account the protection and conservation of their traditions, the evolution of their insertion into mainstream society, such as integration and assimilation, during the process of struggle and adaptation in a foreign land. We have found that, on the one hand, Chinese culture has left an indelible mark on the Cuban society, and, on the other hand, many Chinese cultural elements have evolved to some degree during the transmission process, influenced by the native Cuban culture.